Spatial-temporal and phylogeographic characterization of Trypanosoma spp. in cattle (Bos taurus) and buffaloes (Bubalus bubalis) reveals transmission dynamics of these parasites in Colombia. (2018)
Animal Trypanosomiasis (AT) is one of the most important problems in the Colombian livestock industry reducing its production around 30%. Caribbean and Orinoquia regions play a significant role in the development of this industry, having about 6.9 millio